Implementasi Media Clay dalam Mengembangkan Kreativitas Anak Usia 4-5 Tahun di TK Pembina Pangkalbalam - Meiliandari, Annisa; Yunesti, Dilla (ICEJ : Islamic Childhood Education Journal, 2024)
This research is based on the importance of increasing creative abilities in the cognitive development of children aged 4-5 years through activities using clay media. Thus, it is because the development of clay media that occurs in children has not yet developed and children have not been able to master the cognitive abilities of intelligence and fluency in thinking. Apart from that, in developing children's creativity, almost all of them have developed according to expectations. Therefore, this research explains the implementation of clay media in developing the creativity of children aged 4-5 years at the Pembina Pangkalbalam Kindergarten. The research used by researchers is qualitative research with a descriptive approach method. The data collection technique that the researcher used was in-depth interviews with the principal of the school that the researcher studied and 2 class teachers. And strengthened by observation and documentation of activities during the research. The research subjects were 5 girls and 4 boys. Data analysis techniques are data reduction, data presentation and data verification. The results of the research show that the implementation of clay media in developing the creativity of children aged 4-5 years at Pembina Pangkalbalam Kindergarten shows success with a gradual increase in children's abilities in forming activities using clay. Increased creativity in shaping activities using clay can be seen from indicators covering aspects of child development. Increasing children's abilities in forming activities using clay in the implementation of Developing According to Expectations, children are stated in the indicator that they are starting to be consistent in learning activities and get a 3 star score of 70-79.